AFM investigation of nanomechanical properties of ZnO nanowires. Issue 42 (9th April 2015) - Li, Peifeng; Liao, Qingliang; Wang, Zengze; Lin, Pei; zhang, zheng; Yan, Xiaoqin; Zhang, Yue
Abstract : The mechanical service behavior of ZnO NWs with large scanning angles at a 14.8 mm s −1 scanning rate was studied by AFM. The security service criterion of the NWs was established and the range predicted successfully. The NW modulus and fracture strength were also obtained. Abstract : During the investigation of mechanical properties of nanomaterials by atomic force microscope (AFM), a non-normal stress state with large scanning angles is a universal phenomenon. The mechanical service behaviors of ZnO nanowires (NWs) with diameters ranging from 177 to 386 nm under non-normal stress state were studied by AFM at a scanning rate of 14.8 μm s −1 . We expanded the application scope of the threshold force equation determining the fracture threshold forces of ZnO NWs which was established in our previous work. The criterion equation for security service of ZnO NWs was established by the threshold force equation and force calibration equation. The criterion equation was used to predict the security service range of ZnO NWs successfully. The modulus and fracture strength of the ZnO NWs were also calculated through the fracture threshold force obtained from the threshold force equation. The results have important and meaningful consequences for security practical applications of ZnO NWs under non-normal stress state.